Gypsum Effect on Nitrogen Mineralization and Ammonia Volatilization from Broiler Litter. Issue 6 (27th September 2013) - Mishra, Archana; Cabrera, Miguel L.; Kissel, David E.; Rema, John A.
Abstract : Broiler litter is commonly surface applied to grasslands as fertilizer in the southeastern United States. Surface application may lead to losses of P in surface runoff and to losses of N through NH3 volatilization. Adding gypsum to broiler litter can reduce water‐soluble P and, therefore, the potential for surface water contamination, but no information is currently available on the effect of gypsum on NH3 volatilization when broiler litter is applied to soil. We conducted three laboratory studies to evaluate the effect of adding flue‐gas desulfurization (FGD) gypsum to broiler litter or soil on NH3 volatilized and N mineralized. In two studies, soil with or without 0.01 g FGD gypsum g −1 soil was packed into acrylic columns and broiler litter with or without 0.25 g FGD gypsum g −1 litter was applied on the soil surface and incubated at 25°C for 15 d. In a third study, litter with or without 0.25 g FGD gypsum g −1 litter was mixed with soil and incubated at 25°C for 63 d. Our results showed that the addition of FGD gypsum to broiler litter or soil did not affect net N mineralized or NH3 volatilized when litter was surface applied. Similarly, the addition of FGD gypsum to broiler litter did not affect net N mineralized when broiler litter was incorporated into soil. Thus, the addition of FGD gypsum at these rates does not change NH3 loss or N mineralized from broiler litter.